Conditional Pathways of Support: Sustainability of Coastal Women’s Enterprises through QBL and ToC - MonalisaMonalisa; Asriah Syam; Cindy Yoel Tanesa; Gracela Marisa; Carolina Mustikarini; Afrizal Firman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The blue economy is widely promoted as a pathway to sustainable development, yet women’s enterprises remain marginalized by structural barriers. This study investigates whether support systems directly influence the sustainability of coastal women’s businesses in Bulukumba South Sulawesi, Indonesia, while applying the Quintuple Bottom Line (QBL) and Theory of Change (Toc) frameworks. A quantitative design using survey data from women-led micro, small, and medium enterprises (MSMEs) was analyzed through structural equation modeling (SEM). The model assessed the reliability of constructs and tested the hypothesized effect of support systems including access to finance, social support, and public policy on sustainability outcomes. Findings reveal that although the measurement model demonstrated reliability and validity, support systems showed no significant direct effect on sustainability. This result contrasts with much of the existing literature but aligns with recent studies emphasizing mediation through financial literacy, managerial capacity, and institutional scaffolding. The study thus adds nuance by demonstrating that external interventions, in isolation, are insufficient for sustaining women’s enterprises in coastal contexts. The research contributes theoretically by extending QBL and Toc to gendered coastal entrepreneurship and practically by highlighting the need for integrated, gender-sensitive policies. Future research should examine mediating and moderating mechanisms that translate support into long term sustainability.